Context and Antecedents of Information Utility at the R&D/Marketing Interface - Moenaert, Rudy K.; Souder, William E. (Management Science, 1996)
The objective of the present study was to develop a comprehensive empirically-based model of the communication interface between R&D and marketing. Following Moenaert and Souder (Moenaert, R. K., Souder, W. E. 1990. An analysis of the use of extra-functional information by marketing and R&D personnel review and model. Product Innovation Management 7(3, September) 213–229.), a causal model of the antecedents of information utility at the R&D/marketing-interface was postulated. A non-experimental critical incident method was used to test the model. The field survey involved 386 team members of 80 new product innovation teams in 40 companies. Path analysis was used to test the causal model. Support for several aspects of the model were found. First, the relevance and the credibility of the message had strong effects on the perception of information utility. The comprehensibility of the message had a moderate effect on the perception of information utility, whereas novelty had a small effect. Second, the quality of the relationship, the seniority and the prior experience of the message source, and the type of communication channel used had significant effects on the perception of the message. The implications of the research results for managers and researchers are detailed.